ELECTRON-ION TECHNOLOGY: ENVIRONMENTAL ASPECTS OF ITS APPLICATION IN THE FOOD INDUSTRY - N. S. Nikolaev; V. N. Kornienko; M. Y. Burlev (Современная наука и инновации, 2022)
Development of new and improvement of existing types of equipment implies the intensification, environmental friendliness and energy efficiency of their processes. Studies of various energy effects on raw materials of animal and plant origin have shown that electric technologies are the most promising for intensifying the process of processing raw materials of animal and plant origin. Special attention should be paid to electron-ion technology, namely the process of applying an electric field directly or through the working medium to the processed raw materials. The most relevant issue is the environmental safety of equipment and service personnel, as well as environmental monitoring, where the technology is used using an electric field. The influence of powerful electric fields in the process of inducing electrical impulses, namely, the influence of negative side effects, both in the direction of electromagnetic characteristics and possible x-rays, has not been studied yet. The effectiveness of using electron-ion technology depends on a deep and comprehensive study of the positive and negative aspects of the influence of the electric field on the environmental condition of the product, production and people.